The role of cognitive, emotional, and spiritual development in adult psychological well-being - Mellat, Neda (Journal of spirituality in mental health, 2023)
The purpose of the present study was to examine the relationship between different levels of cognitive, emotional, and spiritual development with adult psychological well-being. A sample consisted of 700 adults in ages (20–60 years). Research data were analyzed using structural equation modeling. The findings showed that relativistic thought affects stress, empathy, and emotion regulation difficulties. Dialectical thought has a positive effect on empathy and spiritual well-being. Egocentrism has a positive effect on emotion regulation difficulties and spiritual weakness and a negative impact on Spiritual well-being. Stress has a positive effect on emotion regulation difficulties. Emotion regulation difficulties positively affect spiritual weakness and negatively affect Spiritual well-being. Empathy has a positive effect on spiritual well-being. Spiritual weakness positively affects aggression, depression, and maladaptive hedonism, it negatively affects altruism. Spiritual well-being negatively affects depression and maladaptive hedonism and positively affects resilience, altruism, and gratitude.